Limited yield penalties in an early transition to conservation agriculture in cotton-based cropping systems of Benin - Yemadje, Pierrot Lionel; Takpa, O'Neil; Amonmide, Isidore; Balarabe, Oumarou; Sekloka, Emmanuel; Guibert, Hervé; Tittonell, Pablo (Frontiers in Sustainable Food Systems, 2022)
Transitioning toward minimum or no tillage is challenging for smallholder farmers in sub-Saharan Africa (SSA), due to the possible yield penalties during the initial years of a transition. Understanding the early impacts of such transitions is crucial in a cash crop such as cotton, on which farmers rely for their income, and is necessary to inform agroecological strategies to cope with both these challenges. This study explores the combined impact of minimum or no tillage and fertilizer regimes on agronomic parameters of cotton–cereal rotations, as practiced by smallholder farmers in Benin. A multilocation experiment was set up in three different agroclimatic zones, namely, Savalou (7°55′41″, 1°58′32″), Okpara (2°48′15″, 7°72′07″), and Soaodou (10°28′33″, 1°98′33″). In each area, the experiment was laid out as a split-plot design with four replications (main plot = soil preparation; subplot = fertilizers regimes). The treatments consisted of three different forms of soil preparation, namely, tillage, strip tillage, and no tillage or direct seeding, and four fertilization regimes, namely, basal mineral fertilizers (BMF, 200 kg ha1 of N14P18K18S6B1 + 50 kg ha1 of urea), BMF + A (200 kg ha1 of calcium phosphate amendment, 22P2O5-43CaO−4S), BMF + C (400 kg ha1 of compost), and BMF + A + C. At all sites, direct seeding led to lower below-ground biomass growth and seed cotton yields compared with conventional tillage in an early transition to conservation agriculture starting from degraded soils (2% to 25%). Weak rooting under direct seeding resulted in lower cotton yields compared with that under tillage (−12%) and strip tillage (−15%). At 45 and 90 days after emergence, cotton plants were shorter under direct seeding compared with tillage (−9% and −13%, respectively) and strip tillage (−23% and −6%, respectively). Fertilizer regimes affected seed cotton yields differently across sites and treatments, with marginal responses within soil preparation methods, but they contributed to increase yield differences between conventional and no tillage. Considering the need for sustainable practices, in the context of degraded soils and poor productivity, such limited yield penalties under CA appear to be a reasonable trade-off in the first year of a transition. Alternatively, the results from the first year of this experiment, which is meant to continue for another 5 years, suggest that strip tillage could be a sensible way to initialize a transition, without initial yield penalties, toward more sustainable soil management.